2014
DOI: 10.1111/cns.12312
|View full text |Cite
|
Sign up to set email alerts
|

Lenti‐GDNF Gene Therapy Protects Against Alzheimer's Disease‐Like Neuropathology in 3xTg‐AD Mice and MC65 Cells

Abstract: GDNF induced neuroprotection in the AD experimental models used. Lentiviral vectors engineered to overexpress GDNF showed to be safe and effective, both as a potential gene therapy and as a tool to uncover the mechanisms of GDNF neuroprotection, including cross talk between astrocytes and neurons in the injured brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 74 publications
2
56
0
Order By: Relevance
“…Instead, the pathology is characterized by gradual increase in the number of amyloid plaques surrounded by chronic neuroinflammation [30] and abnormalities in synaptic microstructure [29]. We found no effect of CDNF treatment on amyloid pathology, which is in line with our earlier observations of no change in brain amyloid load after manipulation of functional TrkB-receptor levels [27] or partial BDNF gene knockout [28], as well as with a recent study reporting lack of effect on amyloid levels by GDNF gene therapy in APP/PS1/tau transgenic mice [9]. Neither could we verify any obvious anti-inflammatory effect of CDNF around the injection site.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, the pathology is characterized by gradual increase in the number of amyloid plaques surrounded by chronic neuroinflammation [30] and abnormalities in synaptic microstructure [29]. We found no effect of CDNF treatment on amyloid pathology, which is in line with our earlier observations of no change in brain amyloid load after manipulation of functional TrkB-receptor levels [27] or partial BDNF gene knockout [28], as well as with a recent study reporting lack of effect on amyloid levels by GDNF gene therapy in APP/PS1/tau transgenic mice [9]. Neither could we verify any obvious anti-inflammatory effect of CDNF around the injection site.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it has reported that 10-month-old 3xTg-AD mice subjected to 6 months of overexpressing GDNF (recombinant lentiviral vectors), showed improvement in the learning and memory. This GDNF neuroprotective effect induced a potent upregulation of BDNF, indicating that together may important against neurons atrophy and degeneration [110].…”
Section: Gdnf and Alzheimer's Diseasementioning
confidence: 96%
“…One of such advances involves gene silencing, one of the main therapeutic approaches, through recruitment of the cellular RNA interference A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 10 (RNAi) pathway. However, some studies have recently reported cellular toxicity caused by short-hairpin RNAs (shRNAs) in mouse and rat brains [47,48].…”
Section: General Advantages and Limitationsmentioning
confidence: 99%